TINJAUAN YURIDIS PERLINDUNGAN KONSTITUSIONAL TERHADAP DEBITOR - Don Saflan; Eddy Asnawi; Robert Libra (LPPM STIH Awang Long, 2025)
Constitutional protection for debtors constitutes a crucial issue within a state governed by the rule of law, particularly following the issuance of Decision of the Constitutional Court Number 02/PUU-XIX/2021, which corrected law enforcement practices related to the execution of fiduciary guarantees. This research aims to analyze the constitutional protection afforded to debtors and the legal consequences arising after the decision, viewed from a constitutional law perspective. The research employs a normative legal research method using statutory, analytical, and historical approaches. The legal materials examined consist of statutory regulations, Constitutional Court decisions, as well as legal doctrines and opinions of legal scholars. The findings indicate that Decision of the Constitutional Court Number 02/PUU-XIX/2021 has significantly strengthened the position of debtors as subjects of law who possess constitutional rights to fair legal certainty, protection from arbitrary actions, and respect for human rights. The decision affirms that debtor–creditor relations are not merely within the realm of private law but are also subject to the principles of the rule of law and constitutional supremacy. The legal implications of the decision include the obligation to adjust statutory regulations, a paradigm shift in law enforcement from formal legal certainty toward substantive justice, and the reinforcement of the Constitutional Court’s role as the guardian of citizens’ constitutional rights. Consequently, this decision serves as an essential constitutional foundation for realizing fair legal protection for debtors in Indonesia.